Design of pectin-chitosan nanoparticles as oral insulin carrier / Syed Mohamad Al-Azi Syed Othman - Syed Othman, Syed Mohamad Al-Azi (2015)
Polymeric nanoparticles are characterized by high risks of premature drug dissolution and low drug encapsulation efficiency. The latter is aggravated by slow nanoparticle formation from large molecular weight polymers due to their slow diffusion kinetics in the reaction medium. This study investigated large molecular weight pectin-chitosan coacervate in insulin encapsulation and sustained release. The nanoparticles were prepared through coacervation of pectin-insulin and chitosan with tripolyphosphate anions in pectin-insulin mixture, or calcium cations in chitosan solution. The formed particles were nanospray-dried when required. The size, zeta potential, morphology, drug content, drug association efficiency, drug release, polymer-polymer and drug-polymer interaction in particulate matrix were examined. Both non-crosslinked and crosslinked pectin-chitosan nanoparticles failed to encapsulate insulin substantially, unless nanoparticles were formed with rapid particle aggregation into micromatrices during coacervation. The aggregation level of nanoparticles can be reduced via spray drying and disaggregation of the particle clusters. These nanoparticles demonstrated fast drug release and chitosan dissolution. The chitosan dissolves readily in intestinal medium and can be utilised to increase mucosal permeability of the promptly released insulin in future endeavour.